2023
DOI: 10.1186/s12902-023-01449-5
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index and cervical vascular function: outpatient-based cohort study

Xiaoyu Pan,
Lin Yue,
Lin Ren
et al.

Abstract: Objectives The purpose of this study was to investigate the correlation between triglyceride-glucose (TyG) index and cervical vascular function parameters in the general population without cerebrovascular disease. Materials and Methods This was a cross-sectional study that recruited a total of 1996 participants without cerebrovascular disease. TyG index was calculated based on fasting triglycerides and glucose. All patients were divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In most studies, the TyG index is usually measured at admission to better predict the incidence or prognosis of HF. However, a study also collected data in the outpatient setting ( 18 ). It was also reported that the TyG-BMI (body mass index), a parameter related to the TyG index and connected with IR, is significantly associated with the risk of developing hypertension ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, the TyG index is usually measured at admission to better predict the incidence or prognosis of HF. However, a study also collected data in the outpatient setting ( 18 ). It was also reported that the TyG-BMI (body mass index), a parameter related to the TyG index and connected with IR, is significantly associated with the risk of developing hypertension ( 19 ).…”
Section: Introductionmentioning
confidence: 99%